A composite adsorption material of floating beads / polydopamine / chitosan and its preparation method and application

By designing the floating bead/polydopamine/chitosan composite adsorption material, using magnetization treatment and multi-layer structure, the problem of low removal efficiency of microplastics and dyes in the existing technology is solved, and efficient and convenient water pollution control is achieved, reducing the number of factors such as the use of magnetization treatment and multi-layer structure. The cost of processing.

CN118925693BActive Publication Date: 2025-01-10DEZHOU UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411424027.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-10-12
Publication Date
2025-01-10
Estimated Expiration
2044-10-12

AI Technical Summary

Technical Problem

Existing water treatment technologies are difficult to effectively remove microplastics and organic dyes, especially small-sized microplastics and activated carbon adsorption methods, which are difficult to regenerate, costly, and unstable biodegradation methods.

Method used

The hybrid bead/polydopamine/chitosan composite adsorption material is used to achieve efficient adsorption of microplastics and dyes through magnetization treatment and multi-layer structure design, and is used multiple times through magnetic separation and physical fishing.

Benefits of technology

It significantly improves the adsorption efficiency of microplastics and dyes, has good recycling convenience and environmental friendliness, reduces treatment costs, and provides an efficient, low-cost and sustainable water pollution control solution.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN118925693B_ABST
    Figure CN118925693B_ABST
Patent Text Reader

Abstract

The present invention relates to the technical field of environmental materials, specifically a floating bead / polydopamine / chitosan composite adsorption material and a preparation method and application thereof, wherein the floating bead / polydopamine / chitosan composite adsorption material has a particle size of 3 mm-10 mm, an adsorption capacity of 52 mg / g-64 mg / g for microplastics, and an adsorption capacity of 86 mg / g-98 mg / g for Congo red dye. Before the material is solidified, the viscous intermediate is precooled and freeze-dried, so that the prepared composite adsorption material has a layered structure feature, significantly improves the specific surface area, and makes the composite adsorption material have good adsorption performance. At the same time, by magnetizing the floating beads, the composite adsorption material can be recycled by magnetic separation, which greatly improves the recycling convenience of the composite adsorption material.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of environmental materials, in particular to a floating bead / polydopamine / chitosan composite adsorption material and a preparation method and application thereof. Background Art

[0002] In recent years, with the acceleration of industrialization and urbanization, microplastics and organic dyes have accumulated in water bodies as environmental pollutants, posing a serious threat to ecosystems and human health. Microplastics refer to plastic particles with a size of less than 5 mm, which are widely present in water bodies such as oceans, rivers, and lakes. They not only affect the health of aquatic organisms, but may also enter the human body through the food chain, posing potential health risks. In addition, organic dyes, as the main pollutants in printing and dyeing, textiles, papermaking and other industries, have high chemical stability and toxicity, and are difficult to completely remove through traditional water treatment methods.

[0003] At present, common water treatment technologies such as flocculation sedimentation, activated carbon adsorption and biodegradation have certain limitations in treating microplastics and dyes. For example, flocculation sedimentation is difficult to effectively remove small-sized microplastics; although activated carbon adsorption has good adsorption performance, it is difficult to regenerate and has high costs; biodegradation requires a long treatment time and the effect is unstable.

[0004] Therefore, a new and efficient solution to control microplastics and dyes in water pollution is urgently needed. Summary of the invention

[0005] The purpose of the present invention is to overcome the shortcomings of the above-mentioned prior art and provide a composite adsorption material of floating beads / polydopamine / chitosan and a preparation method and application thereof. By controlling the size and magnetizing the floating beads, the composite adsorption material can be quickly recovered in a variety of ways; at the same time, the multi-layer structure of the composite adsorption material is utilized to increase the specific surface area, thereby significantly improving the adsorption efficiency of microplastics and dyes.

[0006] In order to achieve the above technical effects, the present invention adopts the following technical solutions:

[0007] A method for preparing a composite adsorption material of floating beads / polydopamine / chitosan comprises the following steps:

[0008] S1. Magnetization of floating beads,

[0009] After pickling, the beads are dispersed in a solution containing Fe 2+ and Fe 3+ In a solution of , adjust the pH and then oscillate to obtain magnetized floating beads;

[0010] S2. Polydopamine coating,

[0011] After coating the magnetic floating beads obtained in step S1 with an interface modifier, the magnetic floating beads are put into a dopamine solution for oscillation polymerization, and the solid is washed and vacuum dried to obtain magnetic floating beads coated with polydopamine;

[0012] S3. Composite adsorption material molding,

[0013] The polydopamine-coated magnetic beads prepared in step S2 are placed in the chitosan solution that has been treated with air bubbles removed, and the mixture is shaken and mixed to obtain a viscous intermediate, and the viscous intermediate is dispersed in a template, and then freeze-dried after pre-freezing to obtain an intermediate product;

[0014] S4. Solidification of composite adsorption material,

[0015] The intermediate product obtained in step S3 is solidified in an alkaline solution, washed, pre-frozen and then freeze-dried to obtain a composite adsorption material of floating beads / polydopamine / chitosan.

[0016] In the preparation method of the composite adsorbent material of floating beads / polydopamine / chitosan provided by the present invention, the viscous intermediate is precooled and freeze-dried before the material is solidified, so that the prepared composite adsorbent material has a layered structure, significantly improves the specific surface area, and makes the composite adsorbent material have good adsorption performance. At the same time, by magnetizing the floating beads, the composite adsorbent material can be recycled through magnetic separation, which greatly improves the recycling convenience of the composite adsorbent material.

[0017] Preferably, in step S1, the pickling treatment steps of the floating beads are as follows:

[0018] The floating beads are firstly washed with alkali to remove surface oil and impurities, then placed in an acidic solution, shaken, taken out and washed with deionized water until neutral, and dried to complete the acid washing treatment.

[0019] More preferably, the acidic solution is a HF solution with a concentration of 5%-10%, the oscillation speed is 100 rpm-200 rpm, and the oscillation time is 5 min-15 min.

[0020] Preferably, in step S1, Fe 2+ and Fe 3+ The molar concentration ratio of the beads and Fe is 1:2. 2+ The feed ratio is (1-3) g:4 mmol; the pH is adjusted to 8-10; the oscillation speed is 150 rpm-200 rpm, and the reaction time is 50 min-70 min; further preferably, the floating beads and Fe 2+ The feed ratio is 2 g:4 mmol.

[0021] Preferably, in step S2, the step of coating the interface modifier with the magnetized floating beads is as follows:

[0022] Take 47.5 parts by volume of 80% ethanol solution, adjust the pH to 7, add 0.05 parts by mass of magnetized floating beads and disperse them evenly, add 0.09 parts by volume of interface modifier and oscillate to react, and the interface modifier is coated after washing.

[0023] More preferably, the interface modifier is tetraethoxysilane, the oscillation speed is 150 rpm-200 rpm, and the reaction time is 8h-12h.

[0024] Preferably, in step S2, the dopamine concentration in the dopamine solution is 1 g / L-2 g / L, the solvent of the dopamine solution is Tris buffer with a pH of 8.5, the ratio of magnetized beads to dopamine solution is 0.1 g:(20-40) mL, the oscillation speed is 120 rpm-180 rpm, and the polymerization time is 12h-24h.

[0025] Preferably, in step S3, the mass concentration of chitosan in the chitosan solution is 1wt%-3wt%, the solvent in the chitosan solution is an acetic acid solution with a volume concentration of 2%-3%, and the mass ratio of the magnetic beads coated with polydopamine to chitosan is 1:(1-3).

[0026] Preferably, in step S3,

[0027] The stirring speed is 150 rpm-200 rpm, and the stirring time is 1h-6h;

[0028] The template is a hemispherical groove with a size of 3 mm-10 mm;

[0029] Pre-freezing is freezing at -40℃~-60℃ for 4h;

[0030] The freeze-drying conditions are freeze-drying at -50℃~-70℃ for 6 h-12 h.

[0031] Preferably, in step S4, the alkali solution is a 5%-10% NaOH solution, and the curing time is 3h-6h;

[0032] Pre-freezing is freezing at -60°C for 4h;

[0033] The freeze-drying conditions are freeze-drying at -50℃~-70℃ for 6 h-12 h.

[0034] The present invention also provides a floating bead / polydopamine / chitosan composite adsorption material prepared by the above preparation method. The floating bead / polydopamine / chitosan composite adsorption material has a particle size of 3 mm-10 mm, an adsorption capacity of 52 mg / g-64 mg / g for microplastics, and an adsorption capacity of 86 mg / g-98 mg / g for Congo red dye.

[0035] By limiting the size of the composite adsorbent material, the composite adsorbent material can not only be recycled through magnetic separation, but also be separated with the help of tools with small pores such as filters, making it convenient for users to operate.

[0036] The present invention also provides the use of the above-mentioned floating beads / polydopamine / chitosan composite adsorption material in adsorbing and treating microplastics and dyes in water bodies.

[0037] Preferably, the adsorption treatment is carried out at 20°C-30°C and 100 rpm-150 rpm of shaking, and the adsorption treatment time is 3h-6h; after the adsorption treatment is completed, the floating beads / polydopamine / chitosan composite adsorption material is recovered.

[0038] The composite adsorption material provided by the present invention comprehensively utilizes the high specific surface area and good adsorption performance of the floating beads, the biocompatibility and multifunctional functional groups of dopamine, and the biodegradability and high adsorption of pollutants of chitosan. Through electrostatic attraction and surface complexation, the composite material significantly improves the removal efficiency of microplastics and dyes. In addition, the present invention effectively utilizes the floating beads in fly ash, turning waste into treasure, and reducing the accumulation of solid waste and environmental pollution.

[0039] At the same time, the composite adsorbent material can be separated magnetically or physically captured and separated according to the size of the adsorbent material, which is more convenient for home use and effectively reduces the processing cost. The composite material will not destroy its original structure during the adsorption process, has stable adsorption performance, and has excellent environmental friendliness. This provides an efficient, low-cost and sustainable solution for water pollution control.

[0040] In this application, the magnetic properties of the beads are ensured in two ways:

[0041] 1) Synthesis: The beads are roughened by acid washing and coated with tetraethoxysilane to ensure that the ferroferric oxide is tightly bound to the beads. At the same time, the feeding ratio of the beads and ferrous / ferric ions is controlled to ensure that the magnetism is sufficient for separation;

[0042] 2) Coating: Ferroferric oxide itself does not react in 2-3% acetic acid solution of chitosan. Subsequent coating with dopamine (coating under alkaline conditions) and chitosan coating protects ferroferric oxide and further ensures the magnetic stability of the composite adsorption material of floating beads / polydopamine / chitosan.

[0043] Compared with the prior art, the present invention has the following beneficial effects:

[0044] The composite adsorption material of floating beads / polydopamine / chitosan provided by the present invention has a layered structure, so that the composite adsorption material has good adsorption performance. At the same time, by controlling the size of the composite adsorption material and magnetizing the floating beads, the composite adsorption material can be magnetically separated and physically caught for multiple uses, which greatly improves the recovery convenience of the composite adsorption material. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 is a SEM image of the floating beads after acid washing during the preparation process of Example 1;

[0046] Figure 2 This is a SEM image of the floating beads coated with Fe3O4 during the preparation process of Example 1;

[0047] Figure 3 This is a SEM image of the magnetized floating beads coated with the interface modifier during the preparation process of Example 1;

[0048] Figure 4 is a SEM image of the magnetized floating beads coated with polydopamine during the preparation process of Example 1;

[0049] Figure 5 is a SEM image of the floating beads / polydopamine / chitosan composite adsorption material prepared in Example 1;

[0050] Figure 6 This is a magnified SEM image of the floating beads / polydopamine / chitosan composite adsorption material prepared in Example 1;

[0051] Figure 7 This is the nitrogen adsorption-desorption curve of the floating beads / polydopamine / chitosan composite adsorption material prepared in Example 1;

[0052] Figure 8 is an infrared spectrum of the floating beads / dopamine / chitosan composite adsorption material prepared in Example 1;

[0053] Fig. 9 is the hysteresis loop of the floating beads / dopamine / chitosan composite adsorption material measured in Example 1;

[0054] Fig.10 is a SEM image of the adsorption material prepared in Comparative Example 1;

[0055] Fig.11 is a SEM image of the adsorption material prepared in Comparative Example 2;

[0056] Fig.12 This is the SEM image of the adsorption material prepared in Comparative Example 4. DETAILED DESCRIPTION

[0057] The present invention will be further described below in conjunction with the accompanying drawings and embodiments.

[0058] The raw materials and experimental equipment used in each embodiment and comparative example are all existing commercially available raw materials and experimental equipment commonly used in the art, and the specific sources are not described here in detail.

[0059] Example 1

[0060] A floating bead / polydopamine / chitosan composite adsorption material is prepared by the following steps:

[0061] S1. Magnetization of floating beads,

[0062] Alkaline washing to remove oil stains: Take 0.1 g of floating beads and add them to 60 mL of 20 g / L NaOH solution. After shaking at 170 rpm for 2 hours, wash the floating beads with deionized water until the washing wastewater is neutral. Dry them in a forced air drying oven at 60°C for 12 hours to obtain floating beads with surface oil stains and impurities removed.

[0063] Acid washing: Place the beads in a 10% HF solution, shake at 170 rpm for 5 minutes, then take them out and wash them with deionized water until the washing wastewater is neutral. Figure 1 As shown, the surface of the floating beads after pickling is rough and has irregular textures.

[0064] Magnetization: After the beads are pickled, 0.0795 g of FeCl2·4H2O powder is dissolved in 25 mL of water, and 0.216 g of FeCl3·6H2O powder is dissolved in 25 mL of water. The two solutions are mixed evenly, and 0.1 g of acid-washed beads are added. The solution is shaken at 170 rpm for 30 min to completely disperse the beads in the solution. The pH is adjusted to 9.0 with 2 M NaOH solution, and the solution is shaken at 170 rpm for 60 min in a 50°C water bath to obtain magnetized beads. Figure 2 As shown, a Fe3O4 layer can be seen covering the surface of the magnetized floating beads.

[0065] S2. Polydopamine coating,

[0066] Coating interface modifier: The magnetized floating beads prepared in step S1 are coated with an interface modifier, and the steps are as follows:

[0067] Add 47.5 mL of 80% ethanol solution to a beaker, adjust the pH to 7.0 with NaOH solution, add 0.05 g of the magnetized beads prepared in step S1, and after oscillation dispersion, mix 0.09 mL of tetraethoxysilane and 2.5 mL of anhydrous ethanol and add dropwise. React at 180 rpm for 10 h. Separate the product by magnetic field and wash with anhydrous ethanol and deionized water. Figure 3 As shown, the magnetized floating beads coated with the interface modifier have no obvious changes compared with the magnetized floating beads.

[0068] Polydopamine coating: dopamine was added to a Tris buffer solution with a concentration of 10 mM and a pH of 8.5 to prepare a dopamine solution with a concentration of 2 g / L. The magnetic floating beads coated with the interface modifier were added and oscillated at 150 rpm for 24 hours. The product was separated by a magnetic field and washed until the washing wastewater was neutral. The product was placed in a vacuum drying oven and dried at 60°C for 12 hours to obtain magnetic floating beads coated with polydopamine. Figure 4 As shown, granular polydopamine appears on the surface of the magnetic beads coated with polydopamine.

[0069] S3. Composite adsorption material molding,

[0070] 0.05 g of chitosan was dissolved in 1.65 mL of 2% acetic acid solution, and after ultrasonic removal of bubbles, 0.05 g of magnetic beads coated with polydopamine obtained in step S2 was added, and stirred at 150 rpm for 1 hour to obtain a viscous intermediate. The viscous intermediate was dispersed in a hemispherical groove template with a radius of 0.5 mm, first frozen at -60°C for 4 hours for pre-freezing, and then transferred to -70°C for freeze-drying for 12 hours to obtain an intermediate product;

[0071] S4. Solidification of composite adsorption material,

[0072] The intermediate product obtained in step S3 was placed in 125 mL of 5% sodium hydroxide solution for solidification for 6 hours, washed until the washing wastewater was neutral, first frozen at -60°C for 4 hours for pre-freezing, and then transferred to -70°C for freeze-drying for 6 hours to obtain the floating beads / polydopamine / chitosan composite adsorption material.

[0073] like Figure 5 and Figure 6 As shown, the prepared floating beads / polydopamine / chitosan composite adsorbent material has a layered structure, which is conducive to the adsorption of microplastics and dyes.

[0074] Figure 7 This is the nitrogen adsorption-desorption curve of the prepared floating beads / polydopamine / chitosan composite adsorbent material. The isotherm belongs to a type IV adsorption isotherm with an obvious hysteresis loop, indicating that the material has a mesoporous structure, which is conducive to the subsequent adsorption of microplastics and dyes.

[0075] Figure 8 This is the infrared spectrum of the composite adsorbent material of floating beads / dopamine / chitosan. The 562 cm -1 The characteristic absorption peak at 3300 cm is caused by the stretching vibration of Fe-O bond. -1 -3500 cm -1 The characteristic absorption peak at 605 cm -1 -696 cm -1The characteristic absorption peak corresponding to the stretching vibration of Si-O bond is located at 1450 cm -1 The absorption peak at 1120 cm -1 The absorption peak at corresponds to the characteristic absorption peak of CN. The above characteristic peaks indicate that the prepared floating beads / polydopamine / chitosan composite adsorption material has abundant surface functional groups, which provides favorable conditions for the adsorption of microplastics and dyes.

[0076] Example 2

[0077] A composite adsorption material of floating beads / polydopamine / chitosan, the preparation steps of which are the same as those of Example 1, and the difference in process parameters is that:

[0078] In step S1,

[0079] During the pickling process, the acid solution used was a 5% HF solution, the oscillation speed was 200 rpm, and the oscillation time was 15 min;

[0080] During the magnetization process, the amount of acid-washed beads was 0.2 g, the pH was adjusted to 10.0, the oscillation speed was 200 rpm, and the reaction time was 70 min;

[0081] In step S2,

[0082] During the coating process of the interface modifier, the amount of the interface modifier was 0.36 mL, the oscillation speed was 200 rpm, and the reaction time was 8 h.

[0083] During the polydopamine coating process, the concentration of dopamine in the dopamine solution was 1 g / L, the amount of dopamine solution was 60 mL, the oscillation speed was 180 rpm, and the polymerization time was 20 h;

[0084] In step S3, the mass concentration of chitosan in the chitosan solution is 2wt%, the solvent of the solution is 3% acetic acid solution, the mass ratio of the magnetic beads coated with polydopamine to chitosan is 1:2, the stirring speed is 180 rpm, the stirring time is 3h, and the mixture is first pre-frozen at -60°C for 4h, and then transferred to -70°C for freeze-drying for 12h to obtain an intermediate product;

[0085] In step S4, the mixture was solidified in 100 mL of 10% sodium hydroxide solution for 3 h, first frozen at -60°C for 4 h for pre-freezing, and then transferred to -50°C for freeze-drying for 12 h to obtain the floating beads / polydopamine / chitosan composite adsorption material.

[0086] Example 3

[0087] A composite adsorption material of floating beads / polydopamine / chitosan, the preparation steps of which are the same as those of Example 1, and the difference in process parameters is that:

[0088] In step S1,

[0089] During the pickling process, the acid solution used was an 8% HF solution, the oscillation speed was 100 rpm, and the oscillation time was 10 min;

[0090] During the magnetization process, the amount of acid-washed beads was 0.3 g, the pH was adjusted to 8.0, the oscillation speed was 100 rpm, and the reaction time was 70 min;

[0091] In step S2,

[0092] During the coating process of the interface modifier, the amount of the interface modifier was 0.54 g, the oscillation speed was 150 rpm, and the reaction time was 12 h.

[0093] During the polydopamine coating process, the concentration of dopamine in the dopamine solution was 1 g / L, the amount of dopamine solution was 120 mL, the oscillation speed was 120 rpm, and the polymerization time was 28 h;

[0094] In step S3, the mass concentration of chitosan in the chitosan solution is 3wt%, the solvent of the solution is 3% acetic acid solution, the mass ratio of the magnetic beads coated with polydopamine to chitosan is 1:3, the stirring speed is 200 rpm, the stirring time is 6 h, and the mixture is first frozen at -60°C for 4 h for pre-freezing, and then transferred to -60°C for freeze-drying for 8 h to obtain an intermediate product;

[0095] In step S4, the mixture was solidified in a 10% sodium hydroxide solution with a volume of 150 mL for 3 h, first frozen at -60°C for 4 h for pre-freezing, and then transferred to -60°C for freeze-drying for 8 h to obtain the floating beads / polydopamine / chitosan composite adsorption material.

[0096] Experimental Example 1

[0097] The hysteresis loops of the composite adsorbent materials obtained in Examples 1 to 3 were measured respectively. Fig. 9 As shown, it is confirmed that the composite adsorption materials prepared in Examples 1 to 3 have sufficient magnetism to achieve magnetic separation, among which the magnetism of Example 2 is the strongest, because at this time the floating beads and Fe 2+ / Fe 3+ The ion ratio is optimal, and more Fe3O4 is coated on the surface of the beads instead of crystallizing in the solution (1 g:4 mmol) or having difficulty in completely coating the beads (3 g:4 mmol).

[0098] Comparative Example 1

[0099] A composite adsorbent material, the preparation method of which is different from that of Example 1 in that after the viscous intermediate prepared in step S3 is dispersed in the template, the pre-freezing and freeze-drying in step S3 are not performed, but step S4 is directly performed to solidify the viscous intermediate in an alkali solution, and the morphology thereof is as follows Fig.10 , it can be seen that the lack of layered structure on its surface is not conducive to subsequent adsorption.

[0100] Comparative Example 2

[0101] A composite adsorbent material, the preparation method of which is different from that of Example 1 in that, after ultrasonically removing bubbles in step S3, 0.1 g of the magnetic floating beads coated with polydopamine prepared in step S2 is added, and the morphology thereof is as follows Fig.11 It can be seen that it is difficult to form a surface layered structure due to the high proportion of magnetic beads coated with polydopamine.

[0102] Comparative Example 3

[0103] A composite adsorption material, the preparation method of which is different from that of Example 1 in that no polydopamine-coated magnetic beads are added, but 2wt% chitosan is directly dissolved in 3% acetic acid solution, dispersed in a mold, pre-frozen and freeze-dried.

[0104] Comparative Example 4

[0105] A composite adsorbent material, the preparation method thereof is different from that of Example 1 in that the pre-freezing condition in step S3 is freezing at -18°C for 4 hours, and the other condition parameters are the same as those of Example 1. Fig.12 ,It can be seen that due to the low pre-freezing temperature, less surface layered structure is formed.

[0106] Comparative Example 5

[0107] A composite adsorbent material, the preparation method of which is different from that of Example 1 in that freeze drying is not used in step S4, but air drying is directly performed, and other parameters are the same as those of Example 1. During the air drying process, the sample loses water and shrinks severely, forming a spherical particle with a smaller particle size, and the same floating bead / polydopamine / chitosan layered structure as in Example 1 cannot be obtained.

[0108] Experimental Example 2

[0109] Adsorption material treatment of microplastics in water

[0110] In this experimental example, the water containing microplastics is 40 mL of a 100 mg / L fluorescent polystyrene microplastic aqueous solution. 20 mg of the adsorption material provided in each embodiment and comparative example was added to the water containing microplastics, and the adsorption was carried out for 3 hours at 25°C and 150 rpm to test the adsorption effect.

[0111] Table 1 Adsorption effect of adsorption materials on fluorescent polystyrene microplastics

[0112]

[0113] In the above table, the calculation method of each data is the residual microplastics in the water mg / L, where and They are the fluorescence intensity of the initial microplastics in the water and the fluorescence intensity of the remaining microplastics in the water after 3 hours of adsorption, which were measured by fluorescence spectroscopy.

[0114] Adsorption capacity = .

[0115] It can be seen from the data in Table 1 that when the various embodiments are compared horizontally, the adsorption capacity also shows some differences. These differences are caused by the chitosan concentration and the magnetic strength of the floating beads during the preparation process. The chitosan concentration affects the integrity and compactness of the layered structure of the floating beads / polydopamine / chitosan composite adsorption material. When the chitosan concentration is 2wt%, the composite layer material has high integrity and moderate intimacy; the stronger the magnetic properties of the floating beads, the stronger the electrostatic attraction and chemical interaction between the surface and the negatively charged microplastics. When the floating beads are combined with Fe 2+ When the mass molar ratio is 2 g:4 mmol, the obtained composite adsorption material has the strongest magnetism. Therefore, the composite adsorption material provided in Example 2 has the best adsorption capacity for microplastics.

[0116] Compared with Comparative Example 1, after the composite adsorption material of floating beads / polydopamine / chitosan is pre-frozen and freeze-dried and then solidified in alkaline solution, its layered structure significantly improves the adsorption capacity of microplastics.

[0117] Compared with Comparative Example 2, Example 1 shows that the addition of polydopamine-coated magnetic beads in excess of the proportion makes it difficult to form a layered structure, thereby reducing the microplastic adsorption capacity.

[0118] Compared with Comparative Example 3, the polydopamine-coated magnetic beads in the composite adsorption material of beads / polydopamine / chitosan not only give the material magnetism, but also further increase the adsorption sites for microplastics, and have better performance than the multilayer structure of pure chitosan, because the layered structure of pure chitosan has a low adsorption capacity for microplastics.

[0119] Compared with Comparative Example 4, Example 1 shows that the low freezing temperature is not conducive to the crystallization of the solvent, and thus is not conducive to the formation of a layered structure on the surface of the floating beads / polydopamine / chitosan composite adsorption material, thereby reducing the microplastic adsorption capacity.

[0120] Compared with Comparative Example 5, freeze-drying in Example 1 can maintain the layered structure on the surface of the floating beads / polydopamine / chitosan composite adsorption material, while air drying will cause the material to lose water and shrink, reducing the microplastic adsorption capacity.

[0121] Experimental Example 3

[0122] Adsorption materials for dye testing in water

[0123] In this experimental example, the dye-containing water body is 10 mL of a 50 mg / L Congo red dye aqueous solution. 5 mg of the adsorption material provided in each embodiment and comparative example was added to the microplastic-containing water body, and the adsorption was carried out for 2 hours at 25°C and 150 rpm to test the adsorption effect.

[0124] Table 2 Adsorption effect of adsorbent materials on Congo red dye

[0125]

[0126] In the above table, the remaining dye in the water 50 mg / L, where and They are the UV absorption intensity of Congo red dye in the initial water and the UV absorption intensity of Congo red dye in the water after 2 hours of adsorption, measured by UV-visible absorption spectrum. Adsorption capacity = .

[0127] It can be seen from the data in Table 2 that when the embodiments are compared horizontally, Example 2 has the highest adsorption capacity for both microplastics and Congo red because Example 2 has the best chitosan concentration and magnetism. Compared with Congo red dye, microplastics have a larger volume, and the surface of microplastics and magnetic beads can produce electrostatic effects, so the magnetism and multilayer structure of the composite adsorbent material will have an impact on the microplastic adsorption process; based on electrostatic attraction and hydrogen bonding, etc., Congo red dye is mainly adsorbed on the surface of chitosan, so the chitosan structure is its main influencing factor, so the adsorption effect of the adsorbent material with a multilayer chitosan structure in each comparative example is better than the adsorption effect of other comparative examples.

[0128] Compared with Comparative Example 1, after the composite adsorption material of floating beads / polydopamine / chitosan is pre-frozen and freeze-dried and then solidified in alkaline solution, its layered structure significantly improves the adsorption capacity of dyes.

[0129] Compared with Comparative Example 2, Example 1 shows that the addition of polydopamine-coated magnetic beads in excess of the proportion makes it difficult to form a layered structure, which is not conducive to the adsorption of microplastics.

[0130] Compared with Comparative Example 3, the magnetic floating beads coated in the floating beads / polydopamine / chitosan composite adsorption material in Example 1 not only give the material magnetism, but also further increase the adsorption sites for the dye, and have more excellent performance than the pure chitosan multilayer structure.

[0131] The reason why the adsorption performance of Comparative Examples 4 and 5 is poor is the same as that of Experimental Example 2.

Claims

1. A method for preparing a composite adsorption material of floating beads / polydopamine / chitosan, characterized in that: The steps include: S1. Magnetization of floating beads, After pickling, the beads are dispersed in a solution containing Fe 2+ and Fe 3+ In a solution of , adjust the pH and then oscillate to obtain magnetized floating beads; S2. Polydopamine coating, After coating the magnetic floating beads obtained in step S1 with an interface modifier, the magnetic floating beads are put into a dopamine solution for oscillation polymerization, and the solid is washed and vacuum dried to obtain magnetic floating beads coated with polydopamine; S3. Composite adsorption material molding, The polydopamine-coated magnetic beads prepared in step S2 are placed in the chitosan solution that has been treated with air bubbles removed, and the mixture is shaken and mixed to obtain a viscous intermediate, and the viscous intermediate is dispersed in a template, and then freeze-dried after pre-freezing to obtain an intermediate product; S4. Composite adsorption material solidification, The intermediate product obtained in step S3 is placed in an alkaline solution for solidification, and after washing, it is pre-frozen and then freeze-dried to obtain a floating bead / polydopamine / chitosan composite adsorption material; In step S1, Fe 2+ and Fe 3+ The molar concentration ratio of the beads and Fe is 1:

2. 2+ The feed ratio is (1-3) g:4 mmol; In step S2, the dopamine concentration in the dopamine solution is 1 g / L-2 g / L, and the ratio of the magnetized floating beads to the dopamine solution is 0.1 g: (20-40) mL; In step S2, the steps of coating the interface modifier with the magnetized floating beads are as follows: Take 47.5 parts by volume of 80% ethanol solution, adjust the pH to 7, add 0.05 parts by mass of magnetized floating beads to disperse evenly, add 0.09 parts by volume of interface modifier and shake to react, and wash to complete the coating of interface modifier; The interface modifier is tetraethoxysilane, the oscillation speed is 150 rpm-200 rpm, and the reaction time is 8h-12h; In step S3, the mass concentration of chitosan in the chitosan solution is 1wt%-3wt%, and the mass ratio of the magnetic beads coated with polydopamine to chitosan is 1:(1-3); In step S4, the alkali solution is a 5%-10% NaOH solution, and the curing time is 3h-6h; In step S3, pre-freezing is freezing at -40°C to -60°C for 4 hours; The freeze drying conditions are freeze drying at -50℃~-70℃ for 6 h-12 h; In step S4, pre-freezing is freezing at -60°C for 4 hours; The freeze drying conditions are freeze drying at -50℃~-70℃ for 6 h-12 h; The prepared composite adsorbent material has a layered structural feature.

2. The preparation method according to claim 1, characterized in that In step S1, the pickling treatment steps of the floating beads are as follows: First, the floating beads are alkaline washed to remove surface oil and impurities, then placed in an acidic solution, shaken, taken out, washed with deionized water until neutral, and dried to complete the acid washing process; The acidic solution is a HF solution with a concentration of 5%-10%, the oscillation speed is 100 rpm-200 rpm, and the oscillation time is 5min-15min; In step S1, the pH is adjusted to 8-10; the oscillation speed is 150 rpm-200 rpm, and the reaction time is 50 min-70 min.

3. The preparation method according to claim 1, characterized in that: In step S2, the solvent of the dopamine solution is Tris buffer with a pH of 8.5, the oscillation speed is 120 rpm-180 rpm, and the polymerization time is 12h-24h.

4. The preparation method according to claim 1, characterized in that: In step S3, the solvent in the chitosan solution is an acetic acid solution with a volume concentration of 2%-3%.

5. The preparation method according to claim 1, characterized in that: In step S3, The stirring speed is 150 rpm-200 rpm, and the stirring time is 1h-6h; The template is a hemispherical groove with a size of 3 mm-10 mm.

6. The composite adsorption material of floating beads / polydopamine / chitosan prepared by the preparation method according to any one of claims 1 to 5, characterized in that: The composite adsorption material of floating beads / polydopamine / chitosan has a particle size of 3 mm-10 mm, an adsorption capacity of 52 mg / g-64 mg / g for microplastics, and an adsorption capacity of 86 mg / g-98 mg / g for Congo red dye.

7. Application of the preparation method as described in any one of claims 1 to 5 in the adsorption treatment of microplastics and dyes in water bodies.

8. The use according to claim 7, characterized in that The adsorption treatment is carried out at 20°C-30°C and 100 rpm-150 rpm of shaking, and the adsorption treatment time is 3h-6h; after the adsorption treatment is completed, the floating beads / polydopamine / chitosan composite adsorption material is recovered.

Citation Information

Patent Citations

  • Magnetic chitosan / polydopamine aerogel as well as preparation method and application thereof

    CN113952899A

  • Fly ash-based magnetic composite material as well as preparation method and application thereof

    CN118059807A